Duration of fever and other symptoms after the inhalation of laninamivir octanoate hydrate: A study of the 2017/18 and 2018/19 seasons and comparison with the 2011/12 to 2016/17 Japanese influenza seasons. Issue 7 (July 2022) - Tani, Naoki; Kawai, Naoki; Ikematsu, Hideyuki; Bando, Takuma; Iwaki, Norio; Takasaki, Yoshio; Shindo, Shizuo; Chong, Yong; Kashiwagi, Seizaburo
Abstract: Introduction: Large scale investigation of the clinical effectiveness of neuraminidase inhibitors for circulating influenza viruses are important along with the surveillance of virus susceptibility in vitro. Methods: The duration of fever and other influenza symptoms as markers of the clinical effectiveness of laninamivir octanoate hydrate (laninamivir) were investigated in the Japanese 2017/18 and 2018/19 influenza seasons and compared with the results of the previous six seasons. Results: Influenza A(H1N1)pdm09, A(H3N2), and B were found in 14, 45, and 52 patients in the 2017/18 season and in 22, 62, and 0 in the 2018/19 season, respectively. The median duration of fever for B was significantly longer than for A(H1N1)pdm09 and A(H3N2) in the 2017/18 season (p = 0.0461) and for A(H3N2) than for A(H1N1)pdm09 in the 2018/19 season (p = 0.0290). However, the differences were subtle in both seasons for other symptoms, with no significant differences in their median duration in comparison of the circulating types/subtypes. Over the eight seasons with the previous six seasons added, the median durations of fever were consistently longer for B than for A, but the relation between the A subtypes was inconsistent. The median durations of fever were comparable over the eight seasons for the virus types/subtypes, as were the median durations of other symptoms. The percentage of febrile patients decreased in a similar pattern over the eight seasons for each type/subtype. Conclusions: The results confirmed that laninamivir has continued to be clinically effective against all types/subtypes of influenza viruses, with no safety issues.